Sexually transmitted infections, sexual risk behaviours and perceived barriers to safe sex among drug users. (30th July 2013) - Islam, M. Mofizul; Topp, Libby; Conigrave, Katherine M.; Haber, Paul S.; White, Ann; Day, Carolyn A.
Abstract Objective : Drug users are at elevated risk of HIV and other sexually transmitted infections (STIs). This study examines prevalence of STIs and perceived barriers to safe sex among drug users accessing low‐threshold primary healthcare in inner‐city Sydney. Methods : Data were extracted manually from clients' medical records and analysed using STATA. Results : Prevalence of HIV, syphilis, chlamydia and gonorrhoea were low (<2%), whereas hepatitis C (62%), hepatitis A (30%), and previous exposure to hepatitis B (25%) were more common. Recent unprotected vaginal and anal intercourse were reported by 85% and 26% of clients, respectively. Younger clients and those with a history of sex work or recent anal intercourse were more likely to report multiple recent unprotected sex partners. Having a regular sex partner was the most prevalent barrier to condom use (37%), and was more likely to be identified by clients who were older, of Indigenous descent, and/or heterosexual. Drug intoxication was a second important barrier (20%), and was more commonly identified by excessive alcohol users. Conclusions : Targeted programs might increase awareness regarding the benefits of condom use and potential sexual risk associated with regular partners. Periodic assessments of alcohol use, and brief interventions for drug users who report problematic use, should also be considered.